The one thing to win at the game of business - Price, Creel (Richmond, Vic. : John Wiley & Sons, 2012)
The One Thing to Win at the Game of Business is the entrepreneur's bible with everything you need to invest in your own entrepreneurial education. Based on author Creel Price's own experience launching a small business for just $10,000 and then selling it a decade later for over $100 million, the book is based on one core business truth: that Decisionship, the ability to make better, faster decisions without the angst, is key to success.
Includes index.
Keywords: Decision making; Management